How Does Deleveraging Affect Funding Market Liquidity? - Qiu, Buhui; Tian, Gary Gang; Zeng, Haijian (Management Science, 2022)
How does deleveraging affect the market liquidity of high-embedded-leverage securities issued by financial institutions and the funding constraints of these institutions? We use the forced deleveraging of structured mutual funds during the 2015 Chinese stock market crash to study the effects of deleveraging. Our regression-discontinuity analysis shows that deleveraging significantly reduces the market liquidity of the deleveraging funds’ equity units. Moreover, our difference-in-differences analysis shows that deleveraging results in large decreases in subsequent fund flows, stock and cash holdings, and performance, with the impact channeled through the deterioration of the market liquidity of the fund’s equity units. This paper was accepted by Victoria Ivashina, finance.